Incredible Utility: The Lost Causes and Causal Debris of Psychological Science - Richters, John E. (Basic and applied social psychology, 2021)
Variable-oriented, sample-based individual differences research strategies and statistical modeling approaches to causal-theoretical inference depend on their logic, coherence, justification, and presumed heuristic value on the tacit assumption that individuals are qualitatively the same, homogeneous with respect to the psychological structures and processes underlying their overt functioning, and that quantitative differences between them are produced by exactly the same psychological structures functioning in exactly the same way within each individual. This psychological homogeneity assumption, however, is demonstrably false and invalidated by a substantial body of uncontested scientific evidence documenting psychological heterogeneity as a ubiquitous, defining characteristic of human functioning. This irreconcilable mismatch between the psychological homogeneity assumption of the paradigm and the psychologically heterogeneous realities of its phenomena renders the individual differences methodology intrinsically incapable of advancing theoretical knowledge about the causes of psychological and behavioral phenomena. A detailed look at this mismatch reveals also that it holds considerable explanatory power as the root cause of the slow theoretical progress and replication failures of psychological research, as well as the driving force behind psychology's inability to relinquish its controversial reliance on null hypothesis significance testing as a justification standard for evaluating theoretical claims.